Efforts to Realize Inclusive Justice through Restorative Justice in the Natuna Islands Community - Marquez, Neilpon Yulinar; Sulaiman , Abdullah (Pusat Publikasi Nusantara, 2025)
Just law enforcement in an archipelago such as Natuna faces various challenges, especially related to limited access to the formal justice system. This study aims to analyze efforts to realize inclusive justice through a restorative justice approach in the Natuna Islands community. Using a normative juridical method, this study examines relevant laws and legal literature that support the application of restorative justice as an alternative dispute resolution. The results indicate that the restorative justice approach can be an effective solution to create more equitable and humanistic justice, emphasizing restoring social relations between perpetrators, victims, and the community. Amidst the limited formal legal infrastructure in the archipelago, this model can provide access to justice that is more easily accessible and follows local values. The application of restorative justice in Natuna can also strengthen community participation in the conflict resolution process while enriching customary law practices that have long been part of the community's social life. This study recommends formal integration between the national legal system and the restorative justice approach, especially in the context of 3T (frontier, outermost, and disadvantaged) areas, to realize inclusive and sustainable justice.